Antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from the clinical setting - OLAWALE OLADEJO BABAYEMI; EBENEZER AYODELE OKE; MICHAEL TOSIN BAYODE (Nusantara Bioscience, 2021)
Abstract. Babayemi OO, Oke EA, Bayode MT. 2021. Antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from the clinical setting. Nusantara Bioscience 13: 239-246. The use of microbial agents to treat infectious wounds based on ethnobotanical knowledge is still minimal. Antibacterial activity of Jatropha tanjorensis J.L.Ellis & Saroja leaf crude extracts and commercial antibiotics were evaluated against bacterial isolates associated with wound samples using agar well diffusion and disc diffusion techniques, respectively. Phytochemical analysis of the sections was carried out using standard methods. Saponin (58 mg/g) was the highest phytochemical in the methanol extract, while flavonoid (0.1 mg/g) was the lowest percentage in the cold water extract. Methanol extract had the highest Zone of Inhibition (ZOI) of 33 mm against Staphylococcus aureus coagulase-positive. In contrast, the lowest ZOI (5 mm) against S. aureus coagulase-positive was obtained from cold water extract. Methanol extract resulted in the highest ZOI ranging from 16 mm to 17 mm against Escherichia coli, while the lowest ZOI was obtained from coldwater extract (3-4 mm). The highest Minimum Inhibitory Concentration (MIC) value of all extracts (100 mg/mL) was obtained against P. aeruginosa, while the lowest MIC value was obtained against coagulase-positive S. aureus (12.5 mg/mL). All extracts contain Octadecanoic acid, n-hexadecanoic acid, and phytol. This study revealed that methanol extract had the highest inhibitory activity against bacteria isolated from wound samples compared to other crude extracts and ciprofloxacin. Therefore, Jatropha tanjorensis could be used as a potent herbal remedy to reduce the adverse effects of wound infection.